Mobility scores as a predictor of length of stay in general surgery: a prospective cohort study. Issue 9 (22nd May 2018) - Carroll, Georgia M.; Hampton, Jacob; Carroll, Rosemary; Smith, Stephen R.
Abstract : Background: Post‐operative length of stay (LOS) is an increasingly important clinical indicator in general surgery. Despite this, no tool has been validated to predict LOS or readiness for discharge in general surgical patients. The de Morton Mobility Index (DEMMI) is a functional mobility assessment tool that has been validated in rehabilitation patient populations. In this prospective cohort study, we aimed to identify if trends in DEMMI scores were associated with discharge within 1 week and overall LOS in general surgical patients. Methods: A total of 161 patients who underwent elective gastrointestinal resections were included. DEMMI scores were performed preoperatively, on days 1, 2, 3 and 30 post‐operative. Statistical analysis was performed to identify any association between DEMMI scores and discharge within 1 week and LOS. Results: Functional recovery (measured by achieving 80% of baseline DEMMI score by post‐operative day 1) was significantly associated with discharge within 1 week. Presence of a stoma was associated with longer LOS. The area under the receiver operating characteristic curve using functional recovery on post‐operative day 1 as a predictor of discharge within 1 week is 0.772. Conclusion: The DEMMI score is a fast, easy and useful tool to, on post‐operative day 1, predict discharge within 1 week. The utility of this is to act as an anticipatory trigger for more proactive and efficient discharge planning in the early post‐operative period, and there is potential to use the DEMMI as a comparator in clinical trials to assess functional recovery.